Achi Jaya Plantation Sdn Bhd / Nur Khaliesa Balqis Hamim - Hamim, Nur Khaliesa Balqis (Faculty Of Chemical Engineering, 2021)
Furthermore, while undergoing industrial training, the trainee 1s able to use the knowledge she gained during her three years at university. Additionally, their soft abilities, such as communication and persuasion, increased as a result of this. Finally, during the internship time, trainees were able to cultivate and promote teamwork. Completing the Internship Program at Achi Jaya Plantation Sdn Bhd was a fantastic experience and a once-in-a-lifetime opportunity. In addition to obtaining knowledge and skills, the trainee was taught to explore, discover, and expose their own abilities. This is also an opportunity for the trainee to develop their technical skills. The Internship Program has exposed the trainee to a working environment in which they must adapt to be a worker rather than just an internship trainee. During this internship, The student learn to be on time, make quick decisions, work with minimum supervision, and obey commands from the supervisor, among other things. It has taught the learner to be more accountable and disciplined in their conduct and work performance. In addition, the trainee can learn a lot by handling the project or work that has been assigned to them. When troubleshooting or preparing something for the process is required, the staff will guide and teach the trainee. The learner appreciated how nice they were and how they never stopped sharing their knowledge. This will assist the student in becoming emotionally and physically prepared before entering the industrial field in the future, particularly when the trainee is required to undertake a significant or essential assignment.